(untitled) (Journal of the College of Basic Education, 2026)
The research problem is defined as: (To what extent are learning outcomes achieved among fourth-year students in the Design course in the Art Education Department according to quality standards?) The research aims to: Identify the targeted learning outcomes in the Design course. Apply an assessment tool to measure the achievement of learning outcomes. Analyze student results and identify strengths and weaknesses. Provide recommendations to improve the quality of education in the Design course. The research population consisted of students in the Art Education Department at the College of Basic Education, Al-Mustansiriya University. The research sample was selected, consisting of (34) fourth-year students, both male and female. The researcher also constructed a form to evaluate cognitive, skill, and affective learning outcomes. The results of the analysis of the evaluation of students’ learning outcomes showed good achievement of the targeted learning outcomes in the Design course according to quality standards, reflecting the efficiency of the curriculum and educational methods used. However, there is a need to strengthen some educational aspects related to practical application, including: Holding training workshops to develop the educational aspect of students. Employing digital design programs in teaching and projects. Promoting a culture of self-assessment and critical thinking. Continuously reviewing and developing assessment tools. In continuation of the current research, the researcher proposes evaluating learning outcomes according to quality standards for students in the Department of Arts Education’s theater course.